Resveratrol, MicroRNAs, Inflammation, and Cancer. (10th August 2011) - Tili, Esmerina; Michaille, Jean-Jacques
Abstract : MicroRNAs are short noncoding RNAs that regulate the expression of many target genes posttranscriptionally and are thus implicated in a wide array of cellular and developmental processes. The expression of miR-155 or miR-21 is upregulated during the course of the inflammatory response, but these microRNAs are also considered oncogenes due to their upregulation of expression in several types of tumors. Furthermore, it is now well established that inflammation is associated with the induction or the aggravation of nearly 25% of cancers. Therefore, the above microRNAs are thought to link inflammation and cancer. Recently, resveratrol (trans-3, 4′, 5-trihydroxystilbene), a natural polyphenol with antioxidant, anti-inflammatory, and anticancer properties, currently at the stage of preclinical studies for human cancer prevention, has been shown to induce the expression of miR-663, a tumor-suppressor and anti-inflammatory microRNA, while downregulating miR-155 and miR-21 . In this paper we will discuss how the use of resveratrol in therapeutics may benefit from the preanalyses on the status of expression of miR-155 or miR-21 as well as of TGF β 1 . In addition, we will discuss how resveratrol activity might possibly be enhanced by simultaneously manipulating the levels of its key target microRNAs, such as miR-663 .